2019
DOI: 10.2139/ssrn.3475379
|View full text |Cite
|
Sign up to set email alerts
|

Coaches on Fire or Firing the Coach? Evidence of the Impact of Coach Changes on Team Performance from Italian Serie A

Abstract: In this paper, football data from the 2007/2008 to 2016/2017 seasons of the Italian Serie A were used to identify the effects of replacing a coach mid-season due to poor team performance. We used an instrumental variable approach to correlate coach turnover within a season with player productivity and found a very low positive impact of the coach change in the short term but a significant negative impact in the long term. Our findings are also relevant to the literature on management replacement in small-size … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 15 publications
0
2
0
Order By: Relevance
“…The results demonstrated that post-dismissal team performance was superior to pre-dismissal team performance. Argentieri, Canova and Manera [ 41 ] analysed a combination of points won, average score of teams during a season and players ratings given by specialized newspapers. The results showed a small but positive impact of the HC change on short term success, but a significant negative impact longer term.…”
Section: Discussionmentioning
confidence: 99%
“…The results demonstrated that post-dismissal team performance was superior to pre-dismissal team performance. Argentieri, Canova and Manera [ 41 ] analysed a combination of points won, average score of teams during a season and players ratings given by specialized newspapers. The results showed a small but positive impact of the HC change on short term success, but a significant negative impact longer term.…”
Section: Discussionmentioning
confidence: 99%
“…Finally, the impact of coach/dean changes is 42 For NFL, business schools and law schools respectively, estimated coefficients (p-values) are -0.06 (0.00), -0.04 (0.64) and -0.08 (0.061). 43 Several papers that seek to test for the impact of coach changes have noted the existence of the Ashenfelter dip in sport team management (Paola and Scoppa, 2012;Bryson et al, 2021;Argentieri, Canova and Manera, 2019).…”
Section: Leadership Changes In the Nfl And Professional Schoolsmentioning
confidence: 99%